Exploring New Learning Paradigms: A Reflection on Barber, Donnelly, and Rizvi (2013): “An Avalanche is Coming: Higher Education and the Revolution Ahead.” - Brown, Tom H. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2015)
Barber, Donnelly & Rizvi (2013): “An avalanche is coming: Higher education and the revolution ahead” addresses some significant issues in higher education and poses some challenging questions to open and distance learning (ODL) administrators, policy makers, and of course to ODL faculty in general. Barber et al.’s paper does not specifically address the area of teaching and learning theories, strategies, and methodologies. In this paper I reflect on the impact that contemporary changes and challenges that Barber et al. describe have on teaching and learning. I draw on earlier work about future learning paradigms and navigationism (Brown, 2006). This provides a fresh approach to survive the revolution ahead with new perspectives and strategies about teaching and learning, strategies which provide meaningful learning opportunities in the future.